Social Skill Anak Usia 5-6 Tahun Di Gorontalo - Rilla Apriana Tamping; Pupung Puspa Ardini; Nunung Suryana Jamin (Student Journal of Early Childhood Education, 2021)
ABSTRACT The study objective is to observe the information regarding the student’s social skills in Group B of TK Indra 1 Hunggaluwa in Limboto Sub-district, Gorontalo District. This study employs a descriptive quantitative method with Group B as the research subject. The data collection techniques include data reduction, data display, and verification. The finding shows that children’s social skill have developed, this is seen from their behavior where children are able to understand and accept the social consequences that exist in the school environment for what they do, and children are also able to take care of themselves. Behavior related to tasks, children are able to ask and answer questions given by the teacher and to follow directions/rules in group activities. In addition, children can show their interpersonal behavior to others include greeting when entering the classroom, having conversations with friends while playing, helping friends who find difficulties in doing their tasks, respecting the work of others. However, from self-behavior, task-related behavior, and also interpersonal behavior, it is identified that some children still need guidance from teachers or others. Keywords: Social Skill; Child; Kindergarten